FRI0482 Cardiac Magnetic Resonance Imaging Reveals Myocardial Fibrosis and Inflammation in Polymyositis/Dermatomyositis Without Cardiac Manifestation: A Pilot Study. (9th June 2015) - Ikumi, N.; Kobayashi, H.; Kobayashi, Y.; Sugiyama, K.; Nagasawa, Y.; Nishiwaki, A.; Nozaki, T.; Inomata, H.; Karasawa, H.; Shiraiwa, H.; Kitamura, N.; Matsukawa, Y.; et al.
Abstract : Background: Polymyositis (PM) and dermatomyositis (DM) are inflammatory diseases; up to 70% affected patients (pts) show cardiac involvement, which may be fatal. However, the diagnosis, based on electrocardiogram, laboratory, and imaging investigations, is difficult because of nonspecific clinical presentation and the lack of standardized criteria. Cardiac magnetic resonance (CMR) is currently the best technique for diagnosing cardiac fibrosis and inflammation. Objectives: To evaluate cardiac involvement in PM/DM pts without cardiac manifestations by using CMR. Methods: Sixteen consecutive female PM/DM pts (age, 51.9±11.0 years; 7 DM, 9 PM) and 16 gender/age-matched healthy controls without cardiac symptoms (age, 52.6±5.3 years) underwent CMR. Pts and control subjects had no history and/or clinical findings of systemic/pulmonary hypertension, coronary artery disease, valvular heart disease, atrial fibrillation, diabetes mellitus, and dyslipidemia. Late gadolinium enhancement (LGE) was considered to indicate myocardial fibrosis, and black-blood T2WI was used for assessing myocardial inflammation. Left ventricular geometry was classified into concentric remodeling, concentric hypertrophy, eccentric hypertrophy, or normal. We compared the pts and controls regarding prevalence of CMR abnormalities, and explored the possible associations between CMR abnormalities and PM/DM disease characteristics. Group comparisons were made using the Wilcoxon chi-square test, Tukey–Kramer test, and Fisher exact test. Results: PM/DM pts had normal inflammatory indices (erythrocyte sedimentation rate, C-reactive protein level), muscle enzyme assays, and improved muscle strength tests. LGE and T2WI were similar between PM and DM. LGE was seen in 8 pts (50%). Three of these 8 pts also had positive T2WI. Enhancement patterns observed were linear in middle layer, linear in subepicardial layer, nodular in middle layer, and patchy in middle layer (3, 1, 3, 1 pts, respectively). T2WI was observed in the same areas with LGE. No difference LGE positivity and T2WI findings was observed between PM (56% and 11%, respectively) and DM (43% and 29%, respectively) pts. Ejection fraction (EF) was similar between pts and controls (p=0.23). Of note, 7 pts showed concentric remodeling, and 75% of these pats showed LGE. PM/DM pts had higher NT-proBNP levels than controls. LGE was significantly correlated with concentric remodeling in PM/DM pts (p=0.04). Anti-Jo1 Ab positivity was correlated with LGE (p=0.03). However, T2WI was not associated with disease characteristics. Adjustment for disease duration, anti-Jo1 Ab, and LGE did not modify the association with concentric remodeling. Conclusions: PM/DM pts without cardiac symptoms have a high prevalence of cardiac abnormalities. PM/DM pts with LGE are associated with abnormal morphology even with normal EF. Moreover, anti-Jo1 Ab positivity may be associated with LGE. Further studies are needed to determine whether CMR abnormalities affect prognosis or treatment strategy. Disclosure of Interest: None declared